2017
DOI: 10.1364/ol.42.001440
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a compressive-sensing Fourier-transform on-chip spectrometer

Abstract: We demonstrate compressive-sensing (CS) spectroscopy in a planar-waveguide Fourier-transform spectrometer (FTS) device. The spectrometer is implemented as an array of Mach-Zehnder interferometers (MZIs) integrated on a photonic chip. The signal from a set of MZIs is composed of an undersampled discrete Fourier interferogram, which we invert using l1-norm minimization to retrieve a sparse input spectrum. To implement this technique, we use a subwavelength-engineered spatial heterodyne FTS on a chip c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…For this analysis we found that a least-squares spectral analysis (LSSA) using the pseudoinverse of the transformation matrix [11,17,19] with an oversampling factor of c = 2.5 provided the best SNR. The pseudoinverse of A is applied to the interferogram, y, to retrieve an estimate,x, of the input spectrum, where y ≈ Ax.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this analysis we found that a least-squares spectral analysis (LSSA) using the pseudoinverse of the transformation matrix [11,17,19] with an oversampling factor of c = 2.5 provided the best SNR. The pseudoinverse of A is applied to the interferogram, y, to retrieve an estimate,x, of the input spectrum, where y ≈ Ax.…”
Section: Resultsmentioning
confidence: 99%
“…The first on-chip SHFTS was proposed in Michelson configuration [10] and was subsequently implemented as an array of MZIs with linearly increasing optical path delays (OPDs) [11][12][13][14][15]. These MZIs constitute a discrete Fourier-transform in which the output of each MZI corresponds to a point in the spatial interferogram.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated photonics enables the design of new FT spectrometer implementations. The most common one consists of an array of MZIs with different optical path lengths (OPDs) [18][19][20][21][22]. Alternatively, [23] uses a single MZI whose OPD can be dynamically increased by using optical switches.…”
Section: On-chip Interrogator Based On Fourier Transform Spectroscopymentioning
confidence: 99%
“…Alternatively, [23] uses a single MZI whose OPD can be dynamically increased by using optical switches. The spectrum can be retrieved by calculating the coefficients of the Fourier cosine series from the interferogram [18,19] or by solving a system of linear equations [20][21][22][23]. However, since the number of MZIs is finite, the retrieved spectrum is an approximation to the actual one and a large the number of MZIs is required in order to achieve a high spectral resolution.…”
Section: On-chip Interrogator Based On Fourier Transform Spectroscopymentioning
confidence: 99%
“…In the last years, using silicon photonics technologies, different approaches have been developed for the demonstration of integrated on-chip spectroscopic systems, such as arrayed waveguide gratings [4], echelle gratings [5] and Fourier-Transform spectrometers (FTS) [6][7][8][9]. Nowadays, many researchers have studied already the FTS based on the silicon-on-insulator (SOI) platform working in the near infrared (NIR) [6,7,9] and short-wave infrared (SWIR) wavelength range [8]. Integrated spatial heterodyne Fourier-Transform spectrometer (SHFTS) with multi-aperture benefits from the high optical throughput, high spectral resolution, and relaxed fabrication tolerances using a phase and amplitude correction algorithms.…”
Section: Introductionmentioning
confidence: 99%